Sevick's transmission line transformers theory and practice - Mack, Raymond A.; Sevick, Jerry (SciTech Publishing, 2014)
The book has thirteen chapters. The topics covered are: transformer basics; ferrite materials; Guanella analysis; Ruthroff analysis; transmission line construction; unun transformer designs; baluns; multimatch transformer; equal delay transformer; simple test equipment; and construction technique.